2002
DOI: 10.1111/j.1745-4522.2002.tb00225.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Studies on Physical Properties of Vegetable Oils and Their Blends After Frying

Abstract: Physical properties of six commonly used oils and three blends consisting of three oils in each blend were studied after three successive frying of ‘poories’(fried snack from flattened dough of refined wheat flour). The changes in viscosity, CIE trans‐reflectance color and related parameters, UV‐Visible spectra and UV‐spectra of oil samples in solvent system (chloroform:methanol; 2:1, v/v) were studied. The results showed that viscosity and color of the oils changed to a much higher extent after first frying t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 10 publications
1
10
0
Order By: Relevance
“…Premavalli et al (1998) investigated the storage and thermal stabilities of refined cottonseed oilmustard seed oil blends (80:20). Comparative studies on physical properties of vegetables oils and their blends after frying indicated a minimization in peroxide value using blended oils (Susheelamma et al 2002). Repeated deep-fat frying was done by using dried potato chips in pure RBO (rice bran oil), SFO (safflower oil) and their model blends to study their thermal behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Premavalli et al (1998) investigated the storage and thermal stabilities of refined cottonseed oilmustard seed oil blends (80:20). Comparative studies on physical properties of vegetables oils and their blends after frying indicated a minimization in peroxide value using blended oils (Susheelamma et al 2002). Repeated deep-fat frying was done by using dried potato chips in pure RBO (rice bran oil), SFO (safflower oil) and their model blends to study their thermal behavior.…”
Section: Introductionmentioning
confidence: 99%
“…A significant decrease of PVs after reaching maximum values confirms that peroxides, which are formed in the early stages of oxidation, are unstable components and are highly susceptible to further changes that result in the formation of secondary products of oxidation (Orthoefer and Cooper 1996). Nevertheless, Susheelamma et al (2002) reported a continuous increase of PV during three successive fryings of a model dough in all investigated samples of oils and blends. Weiss (1970) reported that oil with a PV of 2 meq/ kg is considered to be rancid.…”
Section: Resultsmentioning
confidence: 60%
“…Premavalli et al, (1998) investigated the storage and thermal stabilities of refined cottonseed oil-mustard seed oil blends (80:20). Comparative studies on physical properties of vegetables oils and their blends after frying indicated a minimization in peroxide value using blended oils (Susheelamma et al, 2002). Commercialization has been started in this respect and a few oil blends have already been permitted.…”
Section: Introductionmentioning
confidence: 99%